Cyfrowy nadzór w chińskim modelu autorytarnego kapitalizmu - Olszewska, Karolina (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
This paper examines the rise of digital authoritarianism in the 21st century. In this political regime, the state authorities exercise control over society via digital technologies while governing the national economy based chiefly on free-market principles. The thesis consists of the statement that the elements of the digital economy, including artificial intelligence, digital platforms, and Internet of Things (IoT) communication, are the critical drivers of surveillance capitalism, characterized by unlimited access to any personal and business data. Subsequently, authoritarian governments benefit from possibilities of digital surveillance, including the control of media and the so-called behavioral surplus. It consequently leads to social manipulation, censorship, Internet shutdowns, and different kinds of punishment of citizens via social rating practices. The analysis presents the case study of a model of Chinese digital authoritarianism, taking into account the rising popularity of this kind of regime in other countries, where political power is highly centralized. At the same time, the economic transformation has occurred there due to historical or specific geopolitical conditions. The findings show that the development of digital authoritarianism is a consequence of surveillance capitalism, within which there is a global data flow via digital platforms. Although surveillance capitalism takes more sophisticated forms than digital authoritarianism, it still serves the same purposes of pursuing the interests of the political elites and influential market players, and it could be perilous for the democratic freedoms of citizens.
Keywords: authoritarian capitalism; digital authoritarianism; surveillance capitalism; digital surveillance; digital economy